GERAKAN PEMBERDAYAAN MASYARAKAT (TATHWIR) IKATAN CENDEKIAWAN MUSLIM INDONESIA (ICMI) PADA ERA ORDE BARU HINGGA REFORMASI - M. Fahmi Ashari; Suparto (SHOUTIKA, 2024)
This research aims to understand the community empowerment movement of the Indonesian Muslim Intellectuals Association (ICMI) from the New Order to the Reformation. The research method used is a literature study, which takes research sources from scientific articles, books, and the like. The result of this research is that in the New Order era until the reformation, ICMI experienced organisational dynamics that caused ICMI to lose its role, thus requiring ICMI to revitalise its role in the reformation era. ICMI's role in community empowerment during the New Order era was to establish Bank Muamalat Indonesia, to establish Abdi Bangsa Foundation, to establish Baitul Mal wa Tamwil, to establish Takaful Insurance. In the reform era, ICMI conducted various community empowerment movements, including economic and entrepreneurship programmes, village welfare programmes, community economic development, public health programmes, agribusiness and agro-industry development programmes, education and environmentally friendly energy programmes, and green revolution programmes. The obstacles faced are the lack of activeness of the ICMI board, poor regeneration function. As for the supporting factors, they are the support from the government. Support from Muslim community organisations